The influence of music education on the child’s development - Szűcs, Timea (Array, 2019)
In the international pedagogical literature (Bresler, Catterall, Chapleau, Iwanaga, Miksza), research of the interconnectedness of children’s socioeconomic status, music education, and student performance has been an important field. Such research confirms the presence of major differences between the school performance of students involved and those not involved in music activities, with better performance from those that study music. The basis of analyzing the empirical research was provided by a personally designed and recorded database: “Learning Music in Hungary 2017.” During the survey we used the quantitative method, in the form of a self-completed questionnaire. Hypotheses: 1. I presuppose that learning music can compensate for social disadvantages, which is observable, among others, in better academic performance, and a greater motivation for learning. 2. I presuppose that the children take part in the music related activities in order to achieve social acceptance, apart from the intention to learn how to play an instrument. To test the hypotheses on the compensatory effect of learning music we strove to see whether better academic performance was apparent in the case of children of parents with lower qualifications, too, or whether the academic performance of music learners was better only due to the higher qualifications of the parents. Looking at the findings from the aspect of school subjects it was found that music learners perform better in all subjects, regardless of their parents’ school performance. In primary art schools playing music together, whether chamber music, orchestral, or choral, establishes a special link among the members. The feeling of belonging to a community provides the members with support and a sense of safety, thus it acts as a safety net. In addition, the improvement of several personality traits is facilitated by community life, e.g. accepting the community’s values and norms, mutual support and cooperation.